2012
DOI: 10.1117/1.jbo.17.10.101510
|View full text |Cite
|
Sign up to set email alerts
|

Cellular viscoelasticity probed by active rheology in optical tweezers

Abstract: A novel approach to probe viscoelastic properties of cells based on double trap optical tweezers is reported. Frequency dependence of the tangent of phase difference in the movement of the opposite erythrocyte edges while one of the edges is forced to oscillate by optical tweezers appeared to be highly dependent on the rigidity of the cellular membrane. Effective viscoelastic parameters characterizing red blood cells with different stiffnesses (normal and glutaraldehyde-fixed) are determined. It is shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 17 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…More recently, the dualtrap optical tweezers were used in the micro-rheology applications with the two beams trapping the RBC at its opposite edges, with or without attaching microbeads. With one of the beams oscillating at a small amplitude and a frequency up to 1 KHz to introduce fluctuation, the phase signal of the cell edge displacement vibration was recorded as a function of the oscillation frequency to probe the RBC viscoelastic properties [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the dualtrap optical tweezers were used in the micro-rheology applications with the two beams trapping the RBC at its opposite edges, with or without attaching microbeads. With one of the beams oscillating at a small amplitude and a frequency up to 1 KHz to introduce fluctuation, the phase signal of the cell edge displacement vibration was recorded as a function of the oscillation frequency to probe the RBC viscoelastic properties [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…on two different fibroblast lines . Laser‐induced erythrocyte edge vibrations were employed for probing the viscoelasticity of red blood cells . Ayala et al.…”
Section: Applications For Biological Samplesmentioning
confidence: 99%
“…[163] Laser-induced erythrocyte edge vibrations were employed for probing the viscoelasticity of red blood cells. [164] Ayala et al employed optical tweezers to determine the microrheological properties of fibroblasts, astrocytes, and neurons. [165] Nishizawa et al recently reported a feedback-tracking method for microrheology in mouse fibroblasts and HeLa cells.…”
Section: Microrheology Measurementsmentioning
confidence: 99%
“…The laser beam can also trap the proximity of the cell or vibrate in its position for an active rheology assay. 1,2,5 In a recent paper, we have analyzed the local stress, local strain, and the deformation of a 1-D viscoelastic solid rod and of a 3-D biological cell subjected to an external jumping load at a high frequency using the finite-element method (FEM). 1 In many cases, however, the analysis on the mechanics of the laser beam manipulation of the biological cell was approximate.…”
Section: Introductionmentioning
confidence: 99%